Pendekatan Sibernetika Dalam Hukum: Analisis Presepsi Talcott Parsons Terhadap Dinamika Sistem Nasional Hukum Indonesia - Ramadhani, Laily Fitria; Maromi, Nailul; Tudin, Ahmad Khayat (Media Hukum Indonesia (MHI), 2024)
International law as one of the laws that has often been built by several countries makes a separate foundation in its creation, in this case the law has many roles in the concept of national law, for example in the theory of tallcon person national law in becoming a structure in the development of law that runs in Indonesia, where in the research method in this case using normative juridical so that it can provide a very broad balance in its object. This needs to be explained that national law is one of the materials contained in the theory of customary law and international law.